Sulfate/sulfide removal from wastewater by lab-scale microbial fuel cell - Quynh Hoa, Kieu Thi; Minh Hieu, Phung; Tuan Anh, Vy; Chi Linh, Do; Thi Ngoc Quynh, Nguyen; Thi Dau, Pham; Thi Nga, Vuong; Thi Yen, Nguyen; Van Giang, Nguyen; Xuan Canh, Nguyen (Vietnam Journal of Biotechnology, 2021)
Sulfate/sulfide-containing wastewater is a widespread environmental contaminant resulting from human activities. These pollutants have negative impact on natural ecosystems and human beings. Biological sulfate/sulfide removal can be achieved by reducing sulfate to sulfide with sulfate-reducing bacteria and then oxidizing sulfide to elemental sulfur (So) with sulfide oxidizing bacteria. In sulfate/sulfide contaminant wastewater lacking electron acceptor for sulfide oxidization, excess sulfide will be produced and accumulated in the treatment system. Therefore, microbial fuel cells (MFCs) have been shown to be a promising technique for the removal of sulfate/sulfide pollutants in wastewater. In this study, a lab-scale MFCs has been developed based on the activity of sulfate-reducing bacterium Desulfovibrio. sp. The results showed that sulfate and sulfide removal efficiencies of 74 - 82% (78 ± 2,5%) and 80.8 - 89.1% (~85,6 ± 3,1%) were achieved, respectively, from the 5th day to the 14th day of operation. The voltage of 0.02V and power density of 7.2 to 7.8 mW/m2 was obtained. In this study, sulfide oxidizing-based MFC integrated with sulfate-reducing bioreactor, representing the feasibility of simultaneous sulfate/sulfide pollutants removal and electricity generation in MFCs. This provides a promising treatment system to scale up for its actual applications in sulfate/sulﬁde removal.